Charge transfer to solvent dynamics in iodide aqueous solution studied at ionization threshold. Issue 3 (4th December 2014) - Kothe, Alexander; Wilke, Martin; Moguilevski, Alexandre; Engel, Nicholas; Winter, Bernd; Kiyan, Igor Yu.; Aziz, Emad F.
Abstract : The population of charge-transfer-to-solvent states in iodide aqueous solution can undergo via non-resonant multiphoton electronic excitation above the vacuum level. Abstract : We explore the early-time electronic relaxation in NaI aqueous solution exposed to a short UV laser pulse. Rather than initiating the charge transfer reaction by resonant photoexcitation of iodide, in the present time-resolved photoelectron spectroscopy study the charge-transfer-to-solvent (CTTS) states are populated via electronic excitation above the vacuum level. By analyzing the temporal evolution of electron yields from ionization of two transient species, assigned to CTTS and its first excited state, we determine both their ultrafast population and relaxation dynamics. Comparison with resonant-excitation studies shows that the highly excited initial states exhibit similar relaxation characteristics as found for resonant excitation. Implications for structure and dynamical response of the hydration cage are discussed.